2021
DOI: 10.1021/acs.biomac.1c00896
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Antioxidative Pickering Emulsion Gel through Polyphenol-Inspired Free-Radical Grafting of Microcrystalline Cellulose for 3D Food Printing

Abstract: The manufacture of next-generation 3D-printed foods with personalized requirements can be accelerated by in-depth knowledge of the development of a multifunctional biopolymeric-based ink. As a fat replacer in the food industry, microcrystalline cellulose (MCC) has the potential to address the growing need for sustainable healthy reduced-fat 3D printed foods. The modification of MCC structure by polyphenols gives the way to produce a multifunctional antioxidative Pickering emulsion with improved emulsifying pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 31 publications
5
90
0
Order By: Relevance
“…It has been reported that there is a slight change in the spatial structure and unfolding of the cellulose upon the interaction of functional groups of GA with MCC. 10 As Figure 2 d reveals, the intensity of diffraction peaks decreased more upon the development of a grafted MCC/GA/LAE conjugate, whose RCD dropped down to 58%. The XRD diffractogram showed that the typical MCC peak (2θ = 22.9°) altered to a more diffused peak, showing a reduction in the crystallinity.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…It has been reported that there is a slight change in the spatial structure and unfolding of the cellulose upon the interaction of functional groups of GA with MCC. 10 As Figure 2 d reveals, the intensity of diffraction peaks decreased more upon the development of a grafted MCC/GA/LAE conjugate, whose RCD dropped down to 58%. The XRD diffractogram showed that the typical MCC peak (2θ = 22.9°) altered to a more diffused peak, showing a reduction in the crystallinity.…”
Section: Resultsmentioning
confidence: 89%
“…This could imply an increase in the amphiphilicity of the system upon the grafting process and also the formation of complex coacervates between MCC and LAE. 10 It was stated that the interaction of LAE with other negatively charged molecules leads to the formation of complex coacervates. 29 This finally decreases the efficiency of LAE and therefore reduces the minimum inhibitory concentration of the LAE in certain food and pharmaceutical applications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations